Determination of Sr–Nd–Pb Isotopic Ratios of Rock Reference Materials Using Column Separation Techniques and TIMS - Hui Je Jo (MDPI AG, 2021)
Thermal ionization mass spectrometry (TIMS) can provide highly accurate strontium (Sr), neodymium (Nd), and lead (Pb) isotope measurements for geological and environmental samples. Traces of these isotopes are useful for understanding crustal reworking and growth. In this study, we conducted a sequential separation of Sr, Nd, and Pb and subsequently measured the 87Sr/86Sr, 143Nd/144Nd, 206Pb/204Pb, 207Pb/204Pb, and 208Pb/204Pb ratios of 13 widely used rock certified reference materials (CRMs), namely BCR-2, BHVO-2, GSP-2, JG-1a, HISS-1, JLk-1, JSd-1, JSd-2, JSd-3, LKSD-1, MAG-1, SGR-1, and 4353A, using TIMS. In particular, we reported the first isotopic ratios of Sr, Nd, and Pb in 4353A, Sr and Nd in HISS-1 and SGR-1, and Sr in JLk-1, JSd-2, JSd-3, and LKSD-1. The Sr–Nd–Pb isotopic compositions of most in-house CRMs were indistinguishable from previously reported values, although the Sr and Pb isotopic ratios of GSP-2, JSd-2, JSd-3, and LKSD-1 obtained in different aliquots and/or batches varied slightly. Hence, these rock reference materials can be used for monitoring the sample accuracy and assessing the quality of Sr–Nd–Pb isotope analyses.